2012
DOI: 10.1148/radiol.12112000
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Microvasculature with Acoustic Angiography Yields Quantifiable Differences between Healthy and Tumor-bearing Tissue Volumes in a Rodent Model

Abstract: Purpose:To determine if the morphologies of microvessels could be extracted from contrast material-enhanced acoustic angiographic ultrasonographic (US) images and used as a quantitative basis for distinguishing healthy from diseased tissue. Materials and Methods:All studies were institutional animal care and use committee approved. Three-dimensional contrast-enhanced acoustic angiographic images were acquired in both healthy (n = 7) and tumor-bearing (n = 10) rats. High-spatial-resolution and high signal-to-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 25 publications
2
86
0
Order By: Relevance
“…tortuosity, density) that allow us to discern cancerous tissue from normal tissue [31,32]. Based on previous research that has demonstrated that microvascular remodeling occurs within days after radiation exposure using optical imaging, we hypothesized that quantification of microvascular changes using acoustic angiography may indicate response to therapy sooner than using tumor volume alone, the current clinical standard for assessing response to treatment [9].…”
Section: Discussionmentioning
confidence: 99%
“…tortuosity, density) that allow us to discern cancerous tissue from normal tissue [31,32]. Based on previous research that has demonstrated that microvascular remodeling occurs within days after radiation exposure using optical imaging, we hypothesized that quantification of microvascular changes using acoustic angiography may indicate response to therapy sooner than using tumor volume alone, the current clinical standard for assessing response to treatment [9].…”
Section: Discussionmentioning
confidence: 99%
“…7, the response of the low-frequency transducer was nearly linear at excitation voltages lower than 70 V, having an average transmitting sensitivity of 14.5 kPa/V. nonlinearities showed up when the input was higher than 70 V. at about 100 V, more than 1.2 MPa rarefractional pressure (MI: 0.48) was generated, which was sufficient to produce a high-frequency broadband response from microbubbles imaged in tissue in prior studies [16], [17].…”
Section: B Acoustic Characterizationmentioning
confidence: 96%
“…additionally, a new high-frequency contrast imaging technique, acoustic angiography [16], takes advantage of exciting microbubbles near resonance and detecting their high-frequency, broadband harmonics with sufficient bandwidth separation to achieve both high resolution and high contrast-to-noise ratio (cnr). data has shown that acoustic angiography enables detailed visualization and analysis of microvascular structure [16], [17], and will likely be applicable to vasa vasorum imaging. Thus, we hypothesize that there is a role for contrastenhanced ultrasound imaging in the assessment of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvascular images obtained with such 2 MHz transmission and 30 MHz receiving approach were demonstrated to have very high resolution and contrast to tissue ratios (CTR), producing high quality images similar to x-ray angiography, and thus dual frequency ultra-broadband contrast imaging approach is referred to as "acoustic angiography" [13][14][15].…”
Section: Introductionmentioning
confidence: 99%